2005
DOI: 10.1186/1471-2431-5-35
|View full text |Cite
|
Sign up to set email alerts
|

Equal antipyretic effectiveness of oral and rectal acetaminophen: a randomized controlled trial [ISRCTN11886401]

Abstract: BackgroundThe antipyretic effectiveness of rectal versus oral acetaminophen is not well established. This study is designed to compare the antipyretic effectiveness of two rectal acetaminophen doses (15 mg/kg) and (35 mg/kg), to the standard oral dose of 15 mg/kg.MethodsThis is a randomized, double-dummy, double-blind study of 51 febrile children, receiving one of three regimens of a single acetaminophen dose: 15 mg/kg orally, 15 mg/kg rectally, or 35 mg/kg rectally. Rectal temperature was monitored at baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…About 50% of rectal acetaminophen shortcut the liver. The absorption of acetaminophen suppositories is variable and erratic, and depends on the size of the suppository, its composition, its rate of dissolution, its location on the rectum and the contents of the rectum [6,7]. Rectal acetaminophen undergoes variable hepatic first pass metabolism.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…About 50% of rectal acetaminophen shortcut the liver. The absorption of acetaminophen suppositories is variable and erratic, and depends on the size of the suppository, its composition, its rate of dissolution, its location on the rectum and the contents of the rectum [6,7]. Rectal acetaminophen undergoes variable hepatic first pass metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…They recommended that acetaminophen be administered orally to control fever in children [9][10][11]. Scolnik et al [9] showed no significant difference between the temperatures decrement (the maximum drop in temperature or final temperature or in temperature change during the 3 hours after administration) in children 6 months to 6 years of age treated with 15 mg/kg oral acetaminophen and the same or double dose rectally [7][8][9]. Similarly, in a study by Vernon et al on 37 children aged 3 months to 6 years, no difference in antipyretic effects of oral and rectal acetaminophen at a dose of 15 mg/kg was observed.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations